2021
DOI: 10.1038/s42003-021-02711-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal evaporating droplet dynamics on fomites enhances long term bacterial pathogenesis

Abstract: Naturally drying bacterial droplets on inanimate surfaces representing fomites are the most consequential mode for transmitting infection through oro-fecal route. We provide a multiscale holistic approach to understand flow dynamics induced bacterial pattern formation on fomites leading to pathogenesis. The most virulent gut pathogen, Salmonella Typhimurium (STM), typically found in contaminated food and water, is used as model system in the current study. Evaporation-induced flow in sessile droplets facilitat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 71 publications
1
45
0
Order By: Relevance
“…Earlier, we reported that irrespective of the presence of nutrients, the in vitro viability of wild-type Salmonella inside the sessile droplets is severely compromised post-evaporation. Moreover, the bacteria recovered from dried nutrient-rich sessile droplets hyper-proliferates inside the RAW264.7 macrophages 17 . However, the in vitro viability of bacteria retrieved from the impacted dried droplets on solid surfaces with specific velocities has not been tested before.…”
Section: (G)mentioning
confidence: 98%
See 2 more Smart Citations
“…Earlier, we reported that irrespective of the presence of nutrients, the in vitro viability of wild-type Salmonella inside the sessile droplets is severely compromised post-evaporation. Moreover, the bacteria recovered from dried nutrient-rich sessile droplets hyper-proliferates inside the RAW264.7 macrophages 17 . However, the in vitro viability of bacteria retrieved from the impacted dried droplets on solid surfaces with specific velocities has not been tested before.…”
Section: (G)mentioning
confidence: 98%
“…Earlier, we reported that irrespective of the presence of nutrients, the in vitro viability of wild-type Salmonella inside the sessile droplets is severely compromised post-evaporation. Moreover, the bacteria recovered from dried nutrient-rich sessile droplets hyper-proliferates inside the RAW264.7 macrophages 17 .…”
Section: Fig1mentioning
confidence: 98%
See 1 more Smart Citation
“…We concluded that in Salmonella Typhimurium, OmpA serves dual functions to protect the bacteria from phagocytosis and then help in its survival within macrophages. After entering the host cell, Salmonella resides within a modified phagosomal compartment called Salmonella containing vacuole (SCV) [ 18 ]. The intracellular life and proliferation of Salmonella depend on the stability and integrity of SCV.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of disease transmission, evaporation affects the physiochemical environment inside the microdroplets, for example, osmolality and confinement. These changes affect the metabolism, physiology, and biological activity of the pathogens. The self-secreted secondary metabolites of the microorganisms that stay within the droplets add to the complexity.…”
Section: Introductionmentioning
confidence: 99%